2016
DOI: 10.1177/2325957416686193
|View full text |Cite
|
Sign up to set email alerts
|

Benign Lymphoepithelial Lesion of the Parotid Gland in the Setting of HAART

Abstract: The benign lymphoepithelial lesion is a rare and diagnostically challenging entity. Classically, these lesions present as early manifestation of HIV infection and are rarely seen in those on highly active antiretroviral therapy. We describe 2 rare cases of HIV-associated lympho-epithelial lesions of parotid gland in a 37-year-old female and a 47-year-old male receiving antiretroviral therapy. The lesions were characterized with respect to clinical features, as well as histopathology and radiology findings. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…In other published reports, inflammatory cells such as foamy macrophages, lymphocytes, and plasma cells, epithelial cells, and high-protein material have been identified as LEC content. 8,[11][12][13] Hemorrhagic, keratinized, and infectious content have also been reported. 6,9,14 In this study, hyperintensity on T1-weighted images suggests high cellular density, high protein density, or hemorrhage as the cyst content.…”
Section: Discussionmentioning
confidence: 99%
“…In other published reports, inflammatory cells such as foamy macrophages, lymphocytes, and plasma cells, epithelial cells, and high-protein material have been identified as LEC content. 8,[11][12][13] Hemorrhagic, keratinized, and infectious content have also been reported. 6,9,14 In this study, hyperintensity on T1-weighted images suggests high cellular density, high protein density, or hemorrhage as the cyst content.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoepithelial cysts are benign unilocular or multilocular cysts that can occur in the head and neck region, including the salivary glands. Recently, it was found that patients with HIV can present with multiple and bilateral lesions 10 . Sebaceous lymphadenoma is a rare benign tumor characterized by epithelium with sebaceous differentiation in a background of hyperplastic lymphoid tissue 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Tratando-se de pacientes HIV positivo e lesões bucais, não só linfócitos T CD4 abaixo de 200 cél/mm 3 , como também uma carga viral elevada, higiene bucal precária, uso de tabaco e xerostomia podem contribuir para o desenvolvimento precoce dessas lesões bucais 11,15 .…”
Section: Discussionunclassified